ANALISIS KESALAHAN SISWA KELAS IX DALAM MENYELESAIKAN SOAL STATISTIKA KELAS VIII DI MASA PANDEMI COVID 19 - Kania Tingtrim Wisesa; Marchasan Lexbin Elvi Judah Riajanto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to describe students' errors in solving statistical problems. The research subjects were grade IX students of SMPN 02 CIPONGKOR. The method used in this research is descriptive qualitative. The data used in this study is the result of a test in the form of a statistical description of class VIII consisting of 5 questions and given to the subject of class IX students as many as 20 students. Indicators of Competence Achievement; 1) analyze the data; 2) determine the interquartile range; 3) find the mean; 4) find the median value; The results of this study indicate that there are still many class IX students who have difficulty in solving class VIII questions. The factors that cause many mistakes made by students are lack of mastery of concepts, haste in filling out, difficulty in determining what principle or formula to use and the habits of students who do not answer questions in detail.